Effects of digital public services on trades in green goods: Does institutional quality matter? - Le Thanh Ha; To Trung Thanh (Journal of Innovation & Knowledge (JIK), 2022)
This is the first attempt to examine empirically the effects of the implementation of digital public services (DPS) on the value of trade in green goods (TGG). By applying diverse econometric techniques to a sample of 25 European economies for the period 2012-2019, the results show that DPS captured by three indices (user-centricity, business mobility, and key enabler) has a modest influence on the level of TGG. The results are robust. A higher level of DPS implementation appears to drive up the export value of green goods, and there is evidence of the long-term cointegration of DPS and TGG. Furthermore, the nexus between DPS and TGG is evident in two subsamples of developing and developed economies, but the importance of DPS is more pronounced in the former. Finally, the effects of DPS on TGG value become more significant in the European economies with a well-developed institutional system.
Keywords: F21; G21; O16; C33; 650; Digital public services; European countries; Institutional quality; Trade in green goods